Completely compensated ferrimagnetism and sublattice spin crossing in the half-metallic Heusler compound Mn1.5 FeV0.5 Al - Stinshoff, Rolf; Nayak, Ajaya K.; Fecher, Gerhard H.; Balke, Benjamin; Ouardi, Siham; Skourski, Yurii; Nakamura, Tetsuya; Felser, Claudia (Physical Review B, 2017)
The Slater-Pauling rule states that L21 Heusler compounds with 24 valence electrons never exhibit a total spin magnetic moment. In the case of strongly localized magnetic moments at one of the atoms (here Mn) they will exhibit a fully compensated half-metallic ferrimagnetic state instead, in particular, when symmetry does not allow for antiferromagnetic order. With the aid of magnetic and anomalous Hall effect measurements, it is experimentally demonstrated that Mn1.5V0.5FeAl follows such a scenario. The ferrimagnetic state is tuned by the composition. A small residual magnetization, which arises due to a slight mismatch of the magnetic moments in the different sublattices, results in a pronounced change of the temperature dependence of the ferrimagnet. A compensation point is confirmed by observation of magnetic reversal and sign change of the anomalous Hall effect. Theoretical models are presented that correlate the electronic structure and the compensation mechanisms of the different half-metallic ferrimagnetic states in the Mn-V-Fe-Al Heusler system.
CRIS-Team Scopus Importer:2022-04-14